Review of Vehicle Transportation Procedures on KMP. Gili Iyang Paciran – Bawean Route, East Java Province - Arleiny, Arleiny; Pusriansyah, Ferdinand; Triwahyuni, Siti Nurlaili; Saputra, Dwika Wahyu (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
Paciran Port serves three routes, one of which is from Paciran to Bawean Island with one KMP Gili Iyang. Shipping safety is the reason in this study because several cases of trucks overturning in the vehicle loading space. This study aims to determine the procedures for transporting vehicles on KMP. Gili Iyang. This study uses a qualitative research method with a data collection method using the observation method and then comparing the conditions in the field with existing regulations such as the distance between vehicles, weighbridges, vehicle positions, sterilization of the transportation space, and vehicle tying. This problem uses the legal basis of the Regulation of the Minister of Transportation Number 115 of 2016 concerning Procedures for Transporting Vehicles on Ships. The results of this study are: Paciran Port already has a weighbridge, The ticket after weighing the vehicle only contains the weight of the load, The vehicle loading space is not yet sterile from passengers, The vehicle loading space is sterile from oil spills, The distance between vehicles is still too close and not appropriate, The placement of the vehicle position is still transverse and not appropriate, The mandatory lashing section has not been fully tied. The conclusion of this study is that the procedures for transporting vehicles and placing vehicles on the KMP. Gili Iyang are still not in accordance with the rules stated in the Minister of Transportation No. 115 of 2016. The recommendations given include: the crew of the KMP. Gili Iyang must carry out vehicle transport procedures in accordance with the Minister of Transportation No. 115 of 2016. The need for stricter supervision from the transportation organizer.